Evolving Approaches to the Economics of Public Policy Views of Award-Winning Economists - Kimmel, Jean (W.E. Upjohn Institute, 2016)
For policymakers, economics is a useful tool in the development and evaluation of public policy. And like many sciences, economics is evolving to become more interdisciplinary in its approach. Today, economic theory is often used in conjunction with insights gleaned from psychology and sociology to create a more inclusive, real-world approach to implementing public policy. In this book, five award-winning economists tackle a diverse range of topics and show how applied economics has evolved to give policymakers a more nuanced approach to policy development. The award-winning economists included in this volume are Erica Field, Nancy Folbre, Avner Grief, David M. Kreps, and Michael J. Piore, and the topics they discuss include microfinance, human capital, societal institutions, worker motivation, and workplace regulation.